Snack Product Processing and Business Management of Milkfish Crackers to Increase Local Potential - Endah Susilowati; Diah Hari Suryaningrum; Sari Andayani (Nusantara Science and Technology Proceedings, 2021)
The purpose of the Community Service Program for the Utilization of Science and Technology for the Community (PIKAT) is to provide training and assistance to the "Rojo Mino" Pond Farmers Association Partner Group, which produces processed milkfish. Because all this time, what partners have done with milkfish ponds only sell milkfish products directly without further processing. For this reason, to increase local potential, it is necessary to provide counseling to partners. Based on this, the Community Service Program for the Utilization of Science and Technology for the Community (PIKAT) was carried out to partners to improve knowledge and skills of milkfish processing through training and assistance in making milkfish processed products, financial management of their business, and providing knowledge and enlightenment in strategic management in marketing products with an online system. From the results of this counseling, it was found that the productivity produced by partners in processing milkfish into cracker snack products began to increase in sales. The marketing network that is carried out is increasingly widespread. Thus, the local potential generated by the "Rojo Mino" Pond Farmers Association Partner Group increases.